Valuing increased zinc (Zn) fertiliser-use in Pakistan - Joy, Edward J.M.; Ahmad, Wagar; Zia, Munir H.; Kumssa, Diriba B.; Scott, D.; Young, E.; Ander, Louise; Watts, Michael J.; Stein, Alexander J.; Broadley, Martin R. (Springer, 2016)
Background and Aims: Use of zinc (Zn) fertilisers may be cost-effective in increasing crop yields and in alleviating dietary Zn deficiency. However, Zn fertilisers are underutilised in many countries despite the widespread occurrence of Zn-deficient soils. Here, increased Zn fertiliser-use scenarios were simulated for wheat production in Punjab and Sindh Provinces, Pakistan. Inputs and outputs were valued in terms of both potential yield gains as well as health gains in the population.